Positioning of the knot in the steel wire in relation to the tooth and the Erich bars. Technical note - Simões, Gabriela Maffeis D’Assumpção; Berardi, Rogerio Henrique; Ogoshi, José Lineu Pereira; Horikawa, Fernando Kendi; Snidei, Iron Ricardo Machado; Shinohara, Elio Hitoshi (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Erich bar is a basic technique for restoring occlusal alignment in patients with facial fractures. Although this method is used worldwide, there is no description of what is the best way to stabilize the bar that should be anchored tooth to tooth with steel wire. We describe the method of stabilizing the bar of current use in our Service. We indicate the use of this technique because it stabilizes the bar and, in our opinion, it reduces the need to twist the knots during the patient's return.